PEMANFAATAN TEKNOLOGI UNTUK DESA: E-Village Berbasis Web Menggunakan Framework CodeIgniter di Kantor Desa Pesisir Besuki - Purnomo, Eko; Diana, Nur (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2020)
The 3M protocol (washing hands, wearing masks and keeping a distance) makes community services that interact directly with the community must be limited. The creation of a Web-based E-village is intended to assist in improving village community services, namely services related to writing letters and information about villages, especially during the Covid-19 pandemic. E-viilage is a web-based application developed using an open source application, namely the Codeigniter framework with the MVC model (Model View and Control). The method of research and system development in this study uses the Waterfall model which includes needs analysis, system design, writing program code, program testing, program implementation and maintenance. This application was built using Visual Studio Code with PHP programming language and Codeigniter Framework and supported by MySQL Database. The conculsion of this study are: (1) Web-based E-village application has been produced at the Pesisir Besuki Village Office. (2) This application can help and facilitate community service, namely writing services at the Pesisir Besuki Village Office, from external test results with proper status an 79.2%